Towards the institutionalisation of parliamentary technology assessment: the case for Ireland. Issue 3 (12th August 2014) - Csaki, Csaba; Fitzgerald, Ciara; O'Raghallaigh, Paidi; Adam, Frederic
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to consider the case study of Ireland with regards to the implementation of a formal parliamentary technology assessment (PTA) capability. With emphasis on innovation and knowledge-based economies, society faces a proliferation of technological challenges with far-reaching unpredictable impacts. Elected representatives need unbiased scientific knowledge to underpin evidence-based policy-oriented decision-making. PTA is directed at policy-oriented decision-making processes within the parliament. It identifies the role played by existing agencies and the gaps that remain to be filled in the current landscape. It explores the feasibility of potential future institutional arrangements in a country without a recognised formal PTA agency. Design/methodology/approach – An embedded case study approach was utilised based on three main sources of evidence: relevant published documents pertaining to science and technology governance; interviews with key decision-makers; and illustrative case of "hydraulic fracturing" demonstrating key issues stemming from the lack of a formal PTA structure. Findings – The case revealed the interplay between key actors in the area of science, technology and innovation in Ireland. It demonstrated the need for improved citizen engagement. The analysis revealed that formal technology assessment channels should be established to provide a voice for civil society to engage in policy-making. Given the requirements and constraints, a feasible way to implement PTA seems to be the "parliamentary office" model which would seem to be a good fit in the context of Ireland's current situation. Originality/value – The paper presents how PTA may be realised in a country without a formal PTA agency using a parliamentary office model to provide a channel for citizen engagement in science, technology and innovation (STI) policy-making.